Mexican screen fiction : between cinema and television - Smith, Paul Julian (Cambridge, UK : Polity, 2014)
'Mexican cinema is booming today, a decade after the international successes of Amores perros and Y tu mamtambi{u296E}. Mexican films now display a wider range than any comparable country, from art films to popular genre movies, and boast internationally renowned directors like Alfonso Cuar, Alejandro Gonzez I{u4BA2}arritu, and Guillermo del Toro. At the same time, television has broadened its output, moving beyond telenovelas to produce higher-value series and miniseries. Mexican TV now stakes a claim to providing the most dynamic and pervasive national narrative. This new book by Paul Julian Smith is the first to examine the flourishing of audiovisual fiction in Mexico since 2000, considering cinema and TV together. It covers much material previously unexplored and engages with emerging themes, including violence, youth culture, and film festivals. The book includes reviews of ten films released between 2001 and 2012 by directors who are both established (Maryse Sistach, Carlos Reygadas) and new (Jorge Michel Grau, Michael Rowe, Paula Markovitch). There is also an appendix that includes interviews carried out by the author in 2012 with five audiovisual professionals: a feature director, a festival director, an exhibitor, a producer and a TV screenwriter.'--Page [4] of cover.
Includes bibliographical references (pages [256]-265) and index.
Keywords: Motion pictures -- Mexico -- History; Television programs -- Mexico -- History